Basic Practicum Knowledge of Medical Laboratory Technology Students: A Preliminary Study - Fath Dwisari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine students' perceived knowledge on writing practicum reports. The instrument used in this study was a Likert-scale questionnaire containing 14 items about students' basic knowledge in writing practicum reports from the student's point of view. The results of this study indicate that in general students have tried to write reports according to the manual provided, but some still find it difficult to interpret the results of the practicum, especially in comparing them with references from the literature in the form of theories and previous research. Students are expected to improve their ability to identify patterns and relationships emerging from the results of the practicum. Because researchers about student experiences in writing practicum reports are very rare in Indonesia, this preliminary study will be very useful for those who will research about student experiences in writing practicum reports and can be a foundation in researching the perspectives of instructors/lecturers as well as corpus research discussing the results of student reports.